275 Access to Shade Mitigate Heat Stress and Improves Growth Performance in Lambs During Summer. (8th October 2021) - Joy, Aleena; Dunshea, Frank R; Leury, Brian J; Clarke, Iain J; DiGiacomo, Kristy; Prathap, Pragna; Zhang, Minghao; Chauhan, Surinder S
Abstract: The objective of the present study was to investigate the effects of provision of shade on behavior, physiology, and growth of Merino lambs exposed to natural Australian summer conditions. Sixty Merino lambs were randomly allocated to either pasture with shade (n = 30;paddock with trees) or a pasture without shade (n = 30;paddock without any trees) for one month during southern-Australian summer (February-2021). Sheep were grazing on the pastures as per standard protocols followed on the farm with ad libitum access to water. Lambs were monitored twice daily between 0900-1000h and 1400-1600h to record their behavior, and physiological parameters were recorded on hot days (environmental temperature (T) >30°C). Behavioral patterns were represented as the proportion of animals doing specific activities in each treatment group. Grazing was the most frequent activity observed in animals during morning measurement (> 60% in both groups). However, high temperature (T > 30°C) decreased grazing behavior in sheep to < 5% in both treatments. Standing behavior was significantly greater (65.2 vs 21.6%; P < 0.05) for animals under non-shade treatment, while lying behavior was more frequent (17.3 vs 76.3%; P < 0.01) in animals having access to shade. Significantly more animals were seeking water troughs (P < 0.05) in the non-shade group (33.2%) compared to the shade group (10.3%). On an average hot day (T >28°C), most lambs in the shade group were seeking shade (P < 0.01), and when the temperature exceeded >32°C, 90% of the lambs were seeking tree shade. Sheep with access to shade exhibited lower (P < 0.01) respiration rate (117breaths/min) and rectal temperature (39.7°C) than non-shade group (151breaths/min;40.2°C). Overall, access to shade improved (P < 0.001) average daily gain (+0.047kg/day) in sheep compared to the non-shade group (-0.028kg/day). In conclusion, our research confirms that providing access to shade is an effective ameliorative strategy to mitigate heat-stress in sheep during summer heatwaves.